Camouflage treatment of severe skeletal class III malocclusion with effective torque control in an adolescent combined with forward functional shift and hypodivergent - Ting Yu; Dongmei Lv; Dan Xu; Huiyue Wang; Xin Xiong; Qian Cheng (BMC Oral Health)
Skeletal Class III malocclusion, often presenting with anterior crossbite, significantly affects patients’ oral function, facial aesthetics, and psychological well-being. Here, we report the case of a 17-year-old male patient with a severe skeletal Class III malocclusion, characterized by a concave profile, anterior crossbite, pronounced curve of Spee, and functional anterior shift. The patient preferred a non-surgical approach, posing a challenge for camouflage treatment. The treatment plan involved sequential steps: initially, aligning the maxillary dentition using a mandibular bite block, followed by aligning the mandibular dentition with a maxillary bite block. During this process, uncontrolled torque of the mandibular anterior teeth was observed. To address this, an anterior root torquing spring was applied to control the torque of the lower anterior teeth. Subsequently, a flat bite plane and vertical elastics were utilized to establish proper posterior occlusion. This approach effectively eliminated the functional mandibular shift, resulting in a clockwise mandibular rotation and significant profile enhancement. Throughout treatment, periodontal health was meticulously monitored, ensuring its preservation. Post-treatment outcomes demonstrated well-aligned dentition and correction of the anterior crossbite. At the one-year follow-up, the treatment outcome remained stable.